PENGEMBANGAN DESAIN SPRAYER BUAH MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT - Surya Abdul Muttalib; Agriananta Fahmi Hidayat; Sirajuddin haji Abdillah; Ida ayu Widhiantari; Rozidi Rozidi; Sabar Burhan (The University of Lampung, 2020)
The aim of this research is to develop an specialty sprayer for fruits. It is expected that the sprayer will be able to assist farmers in improving the quality of the fruits. Sprayer is a pesticide applicator that is needed in eradicating and controlling plant pests and diseases. Problems that are often found in the sling type sprayer are the high weight of the sprayer and the short range of spraying so that it is not efficient nor effective for application with high trees. The purpose of this research is to develop the design of fruit sprayer using the Quality Function Deployment (QFD) method. The data generated were analyzed using House of Quality. Results showed that important weight values in the House of Quality analysis included the attributes of the spray lever, easeness of operation and easeness of moving with a score of 4.80, 4.46 and 4.50, respectively. Based on the analysis, the sprayer was developed using a wheel drive system with the addition of wheels and spray levers that can be extended or shortened by adjusting the spray lever knock.